Proses Desain Sistem Informasi Pelayanan Izin Mendirikan Bangungan (IMB) Berbasis GIS - Riya Nur Azizah; Putra Putra; Freddy Sapta Wirandha (Jurnal Ilmiah Teknik dan Sains, 2023)
Building Permit or commonly known as IMB is a permit granted by the Regional Head to building owners in changing, expanding, reducing, or maintaining buildings by applicable administration and technical requirement. IMB is one of legal products which has purpose to create security and safety in building spatial as well as legal certainty. Before building a system, the first step in creating an application is to design and to arrange the design process. The process is carried out on the application or information system concerned. There are 2 methods used in this study, namely direct observation to the field by observing directly the process of storing existing data and observing the transaction process. The second method is a library study which is looking for references and understanding the concept of applying the method to the system created. The IMB service information system design process is arranged based on user needs in using the existing IMB application for information system design process. This information system design process can be developed and implemented in an integrated GIS form. In another word, information system can provide benefits for agencies